New Parameters for Impedance–pH Monitoring in Diagnosing Gastroesophageal Reflux Disease and Predicting its Severity - O. A. Storonova; A. S. Trukhmanov; A. A. Makushina; A. V. Paraskevova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Aim. The present articleidentifies possible correlations between new parameters for impedance–pH monitoring, such as mean nocturnal baseline impedance (MNBI); post-reflux swallow-induced peristaltic wave index (PSPW); and the main parameter, acid exposure time (AET), as well as esophageal motor function. The authors set out to assess the values of MNBI and the PSPW index as additional criteria improving the diagnostic efficacy of impedance-pH monitoring, the completeness of clinical phenotyping of gastroesophageal reflux disease (GERD), as well as determining the probability of a more severe disease course. Materials and methods. A total of 60 patients aged 19 to 71 (mean age 44.7 years) participated in the study: 30 patients with erosive reflux disease (ERD), 30 with non-erosive reflux disease (NERD) and 20 healthy volunteers aged 26 to 65 (mean age 45.2 years). All of them underwent 24-hour combined esophageal impedance–pH monitoring (Gastroscan-IAM, JSC RPE Istok-Sistema, Fryazino) and high-resolution esophageal manometry using a 22-channel water-perfusion catheter (Solar GI MMS, The Netherlands). The authors studied such parameters as AET, GER number, MNBI level, PSPW index, distal contractile integral (DCI), resting pressure in the lower esophageal sphincter (LES), peristaltic break. Statistical processing was performed using Statistica for Windows 10.0 (StatSoft Inc.) and Prism 8 (GraphPad).Results. The examination of patients revealed that MNBI, the PSPW index and DCI significantly decrease with the development of more severe GERD (r = -0.79; p = 0.0000, r = -0.4; p = 0.0002, r = -0.49; p = 0.0000, respectively). A negative correlation was found between AET and the PSPW index (r = -0.38; p = 0.0003) and the MNBI level (r = -0.59; p = 0.0000). A correlation was determined between the value of MNBI and the following parameters: LES resting pressure (r = 0.26; p = 0.0006), DCI (r = 0.35; p = 0.00004), peristaltic break (r = -0.21; p = 0.007), the PSPW index (r = 0.41; p = 0.0000), and GER number (r = -0.59; p = 0.0). A correlation between the PSPW index and DCI (r = 0.22; p = 0.001) was found as well.In the group of ERD patients, the median values of PSPW and MNBI constitute 0.23 [0.17; 0.33] and 1.13 [0.63; 1.53], respectively. Also, a correlation between AET and the MNBI level was found in this group of patients (r=-0.53; p=0.000036). In turn, MNBI correlated with LES resting pressure (r = 0.46; p = 0.0004), DCI (r = 0.36; p = 0.005), peristaltic break (r = -0.37; p = 0.004), and GER number (r = -0,42; p = 0,0000).In the group of NERD patients, the median values of PSPW and MNBI constitute 0.56 [0.51; 0.75] and 3.3 [2.57; 4.8], respectively. A correlation was also found between the MNBI level and AET (r = -0.35; p = 0.005), GER number (r = -0.39; p = 0.00005), as well as between AET and the PSPW index (r = -0.26; p = 0.0000).In the control group, the median values of PSPW and MNBI constitute 0.42 [0.3; 0.5] and 5.83 [5.21; 6.48], respectively. A statistically significant difference (p = 0.02) was found between the median values of MNBI in patients with ERD, NERD, and the control group. A statistically significant difference (p = 0.0) between the median values of the PSPW index in patients with ERD, NERD and the control group was found as well.Conclusions. The revealed correlations between AET, esophageal motor function and new parameters for impedance-pH monitoring allow them to be used as additional criteria improving the diagnostic efficacy of impedance-pH monitoring and the completeness of GERD clinical phenotyping. A decrease in the level of these parameters in patients reflects the probability of a more severe disease course.